Elaboração e avaliação de requeijão cremoso caprino com teor reduzido de lactose para consumo combinado com geleia de goiaba - Gadelha, Gleice Bezerra de Oliveira (2016)
Goat milk is a food with high digestibility and hypoallergenicity but similar in lactose content when compared to cow milk. The Northeast is responsible for a large production of goat milk in Brazil. However, its potential is not yet fully explored. In view of this fact, the objective of this research was to develop and characterize Goat Cream Cheese with reduced content of lactose in order to present a choice of consumption of dairy product combined with guava jelly for the general public, especially for those interested in products with low lactose content. To define the formulations of the Goat Cream Cheese was used CCRD containing eleven test, two independent variables (concentration of fat and lactase) and two dependent (firmness and stickiness). Of these trials, three formulations with reduced content of lactose containing different amounts of lactase and fat were selected through the data obtained by Response Surface Methodology. Were selected those formulations added by 0.7% of lactase and 64% fat (F1), 0.75% of lactase and 62% fat (F2) and 0.8% of lactase and 60% fat (F3). The guava jelly used to be consumed with the product was made with 50% guava pulp. In goat milk, goat cream cheese and jelly were evaluated physical, chemical and physico-chemical aspects, and the final products were also conducted microbiological and sensory analysis. All the results were statistically evaluated using the Analysis of Variance (ANOVA). The Tukey test was used to compare the means, and the frequency histograms for the analysis of sensorial attributes. Microbiological parameters met the standards established by law. The goat cream cheese formulations conteined low fat content, wherein the formulation F3 were considered light in accordance with specific legislation. The sensory evaluation showed that the three formulations were well accepted for all atributes (appearance, color, aroma, taste, consistency, residual taste and overall impression), with no significant difference at 5% significance level. In the test of the ideal, there was a higher percentage of answers indica stronger aftertaste than ideal. There was no significant difference (p> 0.05) in preference test. Given the above, the combination of goat cream cheese with reduced lactose content and guava jelly was well accepted sensorially, presenting itself as a new alternative product derived from goat milk. Furthermore, the product becomes an option for people with lactose intolerance problems.